Financial Performance Analysis Based on Economic Value Added at PT. Pertamina Hulu Energi - Sonia Aprilia; Sandra Adelia; Harmoni Delarossa; Addya Nafisa; Tria Oktavina; Aulia Devita Ramadhan; Faisa Putra; Yossinomita Yossinomita (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the financial performance of PT Pertamina Hulu Energi using the Economic Value Added (EVA) method during the 2020-2024 period. This study uses a quantitative descriptive approach with secondary data obtained from the company's annual reports and the corrected EVA calculation workbook. The analysis technique was carried out through calculations of the effective tax rate, Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital (WACC), Capital Charge, and Economic Value Added. The results show that EVA in 2020 was in a negative condition of USD -68,14 million, while EVA in 2021-2024 was in a positive condition. The highest EVA occurred in 2022 at USD 3.205,76 million. These findings indicate that PHE was able to create economic value added after 2020 because the NOPAT generated exceeded the cost of capital used. Keywords: Financial Performance; Capital Charge; EVA; NOPAT; WACC;